Finding inspiration in the making of Tunjukkan Kami Jalan Yang Lurus: Siri Fotografi I & II / Mohammad Firdaus Azman - Azman, Mohammad Firdaus (UiTM Perak Press, 2021)
Tunjukkan Kami Jalan Yang Lurus: Siri Fotografi I & II is a work produced against the backdrop of a straight road landscape. This location is taken in an area located in the state of Perlis. This photography was processed in a panoramic technique and was photographed in black and white. In addition to capturing the subject accurately, this series of photographs is produced with difficulty to be descriptively accurate and neutral in an interpretive and evatative manner (Barret, 2006). This work was adapted from the artist’s experience in navigating the world of learning to the ivory tower. The verse Tunjukkan Kami Jalan Yang Lurus (meaning “Keep us on the right path”) itself encompasses the artist’s memory of all those involved in teaching and educating themselves to become one of the successful and useful human beings today. With the permission of Allah S.W.T, the sacrifices of teachers and educators who contribute to what artists have today are a service that will never be forgotten. Be a motivation and inspiration for the artist to get on with life.